Equine Programs for Military Veterans and RCMP Officers with Occupational Stress Injuries: A Qualitative Analysis - Buchanan, Marla J.; Haney, Colleen; Grimes, Katie N. (Canadian Journal of Counselling and Psychotherapy, 2021)
Alternative approaches to mental health and support programming for military veterans and for officers of the Royal Canadian Mounted Police (RCMP) with occupational stress injuries have recently received attention in the field of post-traumatic stress. The purpose of this study was to evaluate the experiences of military veterans and actively serving RCMP officers with occupational stress injuries who participated in an exploratory study using an equine-assisted learning program. Using a focus group research design, 20 veterans and five RCMP officers were interviewed about their experiences in a 4-week equine-assisted learning program. A thematic content analysis, following Braun and Clarke’s (2006) method, revealed five main themes: (1) appreciation for the value of learning new skills, (2) connection with the horse in terms of the human–animal bond, (3) self-regulation and learning to “speak horse,” (4) sense of accomplishment and competence, and (5) transferable skills to everyday life. The qualitative findings of this study provide support for the use of equine-assisted learning programming with military veterans and RCMP members and demonstrate potential as an alternative therapeutic intervention for occupational stress injuries in these populations.